Stopping wolves in the wild and legitimizing meat consumption: Effects of right-wing authoritarianism and social dominance on animal-related behaviors. (September 2019) - Becker, Julia C.; Radke, Helena R. M.; Kutlaca, Maja
In the present research, we applied the dual process model of ideology and prejudice to beliefs and behavioral intentions toward animals. In Study 1 ( N = 126), we demonstrate in a community sample that right-wing authoritarianism (RWA) predicts support for restricting the distribution of wolves and bears in the wild mediated by perceived threat elicited from the animal outgroups. In contrast, social dominance orientation (SDO) had an indirect effect on the legitimization of meat consumption via endorsement of human supremacy beliefs. In Study 2 ( N = 223), we examined the causal direction of the dual process model using an experimental approach. Results show that RWA predicts support for restricting the free movement of a new animal species in the wild only when it is perceived to be threatening for humans. However, SDO predicted perceived legitimacy of meat consumption, regardless of whether the new animal species was characterized as lower or higher in status compared to other animals. Implications of these findings are discussed.